Rancang Bangun Aplikasi Presensi Tutor Tendik PKBM Hidayah Probolinggo Berbasis Web - Irwan Hadi Pratama; Lamsadi; Bambang Hariyadi (CV. ITTC INDONESIA, 2025)
The development of information technology has driven the digitalization of various aspects of educational management, including attendance systems for educators. At PKBM Hidayah, Kota Probolinggo, attendance recording is still conducted manually, resulting in delays in data recapitulation, potential recording errors, and low efficiency and transparency. This study aims to design and develop a web-based attendance application to improve the efficiency and accuracy of recording the presence of tutors and education staff. The research method used is the SDLC (System Development Life Cycle) model. Data collection techniques employed include observation, interviews, and document studies. For application development, the waterfall method is applied to build the attendance application. This system is expected to provide a modern solution for managing educator attendance within PKBM and other non-formal educational institutions, ensuring better data accuracy, faster processing, and improved transparency in administrative processes.